A META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS OF PDE5 INHIBITOR SILDENAFIL IN THE TREATMENT OF HEART FAILURE WITH PRESERVED EJECTION FRACTION. (June 2022) - Sun, Runmin; Wang, Qiongying; Yu, Jing
Abstract : Objective: he results of clinical trials of phosphodiesterase (PDE) 5 inhibitors for the treatment of HFpEF patients are inconsistent. Thus, we undertook a meta-analysis to evaluate the clinical value of sildenafil for HF with preserved EF (HFpEF) patients. Design and method: Relevant studies were searched and identified in the PubMed, Cochrane Library and EMBASE databases. We searched andomised controlled trials (RCTs) that compared PDE5i with placebo in HFpEF and extracted relevant clinical data. Results: Six RCTs enrolling 471 HFpEF patients were included in the meta-analysis.Compared with placebo, sildenafil was not significantly associated in death (OR = 1.12, 95%CI: 0.06 to 19.40), adverse events (OR = 2.55, 95%CI:0.67 to 9.62) .Also, sildenafil therapy had no impact on the patient's six-minute walk test, PASP, E/e', peak VO2, NT-proBNP but improved at PVR(SMD = -1.04, 95% CI = -1.96 to -0.13) significantly compared to placebo in HFpEF patients. Whereas, if only the RCT study with HFpEF combined with pulmonary hypertension is included, sildenafil therapy was associated with a marked improvement in E/e' (SMD = -0.745, 95% CI = -1.24 to -0.25) in HFpEF patients combined with pulmonary hypertension. Conclusions: Compared with placebo, sildenafil therapy was associated with the improvement of diastolic function in HFpEF patients combined with pulmonary hypertension, while sildenafil treatment of HFpEF patients does not increase death or rehospitalization.